2023
DOI: 10.1136/jnis-2023-020173
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline embolization device versus Atlas stent assisted coiling for intracranial aneurysm treatment: a retrospective, propensity score matched study with a focus on midterm outcomes and hospital costs

Abstract: BackgroundStent assisted coiling (SAC) and flow diverters (FDs) are common endovascular treatments for wide necked cerebral aneurysms, but studies comparing the new generation Atlas SAC and FDs are scarce. We performed a propensity score matched (PSM) cohort study to compare the Atlas SAC and the pipeline embolization device (PED) for proximal internal carotid artery (ICA) aneurysms.MethodsConsecutive ICA aneurysms treated at our institution with either the Atlas SAC or PED were studied. PSM was used to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…There were no significant differences in the rates of aneurysm occlusion (89.9% vs 86.5%, p=0.486), total complications (5.6% vs 11.2%, p=0.177), or favorable functional outcome (96.6% vs 97.8%, p=1.0) between the Atlas and PED groups. 35 The high occlusion rates in our study and the available literature suggest that SAC with the Atlas device remains an efficacious strategy for ICA aneurysm treatment.…”
Section: Discussionmentioning
confidence: 55%
“…There were no significant differences in the rates of aneurysm occlusion (89.9% vs 86.5%, p=0.486), total complications (5.6% vs 11.2%, p=0.177), or favorable functional outcome (96.6% vs 97.8%, p=1.0) between the Atlas and PED groups. 35 The high occlusion rates in our study and the available literature suggest that SAC with the Atlas device remains an efficacious strategy for ICA aneurysm treatment.…”
Section: Discussionmentioning
confidence: 55%
“…The rate of thromboembolic events associated with the NeuroForm Atlas stent was lower than that associated with the LVIS device (4.9%), Neuroform (6.7%) and Enterprise (5.9%) stents according to a meta-analysis [ 24 , 25 ]. A study comparing the complication rates of Pipeline and Atlas stent implantation for aneurysms showed that the midterm complication rates of the PED and Atlas SAC for the treatment of ICA aneurysms were similar (5.6% vs. 11.2%, P = 0.177) [ 26 ]. However, there are few studies focused on identifying the risk factors of ischaemic stroke and stent thrombosis following Atlas stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch et al [ 22 ] reported an incidence of 1.4% for intraprocedural rupture or vessel dissection and 1.0% for periprocedural or early haemorrhage. A study in China reported that the incidence of haemorrhagic complications was 1.4% [ 26 ]. According to a multicentre postmarket analysis, 2 patients (1.6%) experienced haemorrhagic complications, with one experiencing complications during the procedure and the second experiencing complications during the postoperative follow-up period [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundant comparisons of FDs with BS or LCS in the literature [ 37 , 38 , 39 , 42 , 43 , 44 ], to be able to determine the level of flow diversion provided by BS specifically, the inclusion of an LCS (as a reference) arm, a BS arm, and an FD separately in the same cohort is crucial; otherwise, the extent of the flow diversion provided by BS would remain undisclosed. Such a comparison has not been performed previously, but it does have clinical relevance: Stent monotherapy and suboptimal coiling (undercoiling) have been proposed as BS-based endovascular treatment alternatives, despite the lack of clear evidence as to the flow diversion capacity of these stents [ 29 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%